Microglia damage precedes major myelin breakdown in X‐linked adrenoleukodystrophy and metachromatic leukodystrophy. Issue 6 (11th February 2019) - Bergner, Caroline G.; van der Meer, Franziska; Winkler, Anne; Wrzos, Claudia; Türkmen, Mevlude; Valizada, Emil; Fitzner, Dirk; Hametner, Simon; Hartmann, Christian; Pfeifenbring, Sabine; Stoltenburg‐Didinger, Gisela; Brück, Wolfgang; et al.
Abstract: X‐linked adrenoleukodystrophy (X‐ALD) and metachromatic leukodystrophy (MLD) are two relatively common examples of hereditary demyelinating diseases caused by a dysfunction of peroxisomal or lysosomal lipid degradation. In both conditions, accumulation of nondegraded lipids leads to the destruction of cerebral white matter. Because of their high lipid content, oligodendrocytes are considered key to the pathophysiology of these leukodystrophies. However, the response to allogeneic stem cell transplantation points to the relevance of cells related to the hematopoietic lineage. In the present study, we aimed to better characterize the pathogenetic role of microglia in the above‐mentioned diseases. Applying recently established microglia markers to human autopsy cases of X‐ALD and MLD we were able to delineate distinct lesion stages in evolving demyelinating lesions. The immune‐phenotype of microglia was altered already early in lesion evolution, and microglia loss preceded full‐blown myelin degeneration both in X‐ALD and MLD. DNA fragmentation indicating phagocyte death was observed in areas showing microglia loss. The morphology and dynamics of phagocyte decay differed between the diseases and between lesion stages, hinting at distinct pathways of programmed cell death. In summary, the present study shows an early and severe damage to microglia in the pathogenesis of X‐ALD and MLD. This hints at a central pathophysiologic role of these cells in the diseases and provides evidence for an ongoing transfer of toxic substrates primarily enriched in myelinating cells to microglia. Main Points: Immune‐phenotyping of microglia allows a more precise assessment of lesion evolution in leukodystrophies. Microglia cell death is a seminal early feature in X‐ALD and MLD. Cell death pathways differ according to the diseases and lesion stages.